Repetisi pada Lirik Lagu Dangdut Karya Denny Caknan (Repetition in the Lyrics of Dangdut Songs by Denny Caknan) - Muhammad Fatahillah; Sumarlam Sumarlam (Translation and Linguistics (Transling), 2025)
This research aims to understand and describe the phenomenon of repetition in six popular songs by Denny Caknan. This study employed a descriptive qualitative method, using content analysis and a discourse analysis approach referring to Sumarlam (2024). The data were collected through listening and note-taking techniques from the lyrics of Denny Caknan's songs, specifically from his YouTube channel, DC Musik. The songs analyzed include "Kartonyono Medot Janji," "Sugeng Dalu," "Los Dol," "Angel," "Satru," and "Kalih Welasku." The findings reveal 35 instances of repetition across the selected songs. Five types of repetition were identified: epizeuxis (10 data), anaphora (1 data), epistrophe (1 data), epanalepsis (1 data), and full repetition (22 data). "Kartonyono Medot Janji" contained the most repetitions. The dominant types of repetition found were full repetition and epizeuxis. The use of repetition in Denny Caknan's songs serves to emphasize specific messages. This study is expected to provide insights for future research on discourse analysis, particularly concerning repetition in song lyrics.